The Characterization of Fortified Rice (Fortivit) and Biofortified Rice (Nutri Zinc): Karakterisasi Beras Fortifikasi (Fortivit) dan Beras Biofortifikasi (Nutri Zinc) - Sonya Mamoriska; Moch Gelar Hidayat; Cynthia G. Magda; Astri Yuliarti; Eny Cahyaningsih; Eriel Manalu; sambudi sambudi; Rista Yulia Kusuma Putri (Perum BULOG, 2022)
In overcoming Iron Deficiency Anemia and stunting, the Indonesian government seeks to increase the content of iron (Fe) and zinc (Zn) in milled rice through fortification and biofortification. Fortivit rice is rice fortification produced by BULOG. Inpari Nutri Zinc is biofortified rice grown from plant breeding by the Ministry of Agriculture, which ID Food currently produces. This study is a continuation of the IFFRI research collaboration on the Implementation and Research of Precision Agriculture in Biofortified Rice Strain. This study aimed to characterize the biofortified rice as a result of fertilization recommendations in previous studies and compare biofortified rice with fortified rice in several aspects, including micronutrient contents especially Zn, organoleptic, and production costs. The highest Zn content of Nutri Zinc was found in the aleuron, so that the post-harvest process caused a decrease in Zn level. The differences in fertilization recommendations have an impact on the Zn content in brown rice, each layer of aleurone, and the rice endosperm. The nutritional content of Fortivit and Nutri Zinc rice was relatively the same as non-fortified/biofortified rice. The washing and cooking process caused a decrease eof about 4 percent in Zn content in fortified rice, while in biofortified rice, there was relatively no decrease. Although there was a decrease in Zn in fortified rice, overall, the Zn content was still much higher than in biofortified rice. Based on the results of the hedonic test, fortifed rice (Fortivit) was the most preferred for all sensory attributes. In biofortified rice (Nutri Zinc), respondents prefer the rice with 100 percent milling grade the most. Fortivit rice had a faster research time and a lower estimated cost in research. In the contrary, it had a higher estimated cost in production than Nutri Zinc rice. Nonetheless, the selling price of Fortivit rice is cheaper than Nutri Zinc rice on the market. keywords: rice, fortification, biofortification, Fe, Zn